Diffraction of water waves in water of variable depth - Jesada Jiraporn; Shuto, Nobuo; IBM (Thailand) Co. Ltd. (Bangkok : Asian Institute of Technology, 1971)
A numerical technique of solving the problem of diffraction of water waves passing through a breakwater gap in water of variable depth was devised. The technique was applied to the problem in which the bottom slope is constant, the breakwaters are on a contour line, the direction of propagation of the incident waves is perpendicular to the breakwaters and the gap width is of two wavelengths of the incident waves at the gap. The results were compared with the experimental results obtained by Ismail Mobarek.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1971
Keywords: Waves; Hydrodynamics